Innovative technologies for autism: critical reflections on digital bubbles. Issue 2 (15th June 2015) - Parsons, Sarah; Yuill, Nicola; Brosnan, Mark; Good, Judith
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – There is increasing interest from researchers, teachers and other professionals, individuals with autism, and families about the potential for innovative technologies to transform learning experiences and facilitate friendships and social networks. Media accounts have highlighted both the apparently miraculous impacts of technology on supporting communication and learning for people with autism, as well as significant concerns about whether technology use is healthy, safe and socially appropriate for children and young people. Rarely, however, is any evidence reported to support either set of claims. The paper aims to discuss these issues. Design/methodology/approach – This short paper reports on an Economic and Social Research Council-funded seminar series in the UK that is critically reviewing and discussing the field with respect to the research evidence base but also the assumptions that are made about where, how and whether innovative technologies may be useful for people with autism and their families. Findings – The first seminar in the series focused on whether technologies create a social bubble for people with autism and presented research demonstrating that technology use can be positive, supportive and rewarding. Originality/value – This paper offers an up-to-date insight into some of key debates about the benefits and limitations of social technologies for people with autism. Its value lies in raising questions about, and discussing evidence that challenges, some of the negative assumptions that are often perpetuated by the media about the potentially harmful effects of technologies.